Comparative Analysis of the Complete Plastomes of Apostasia wallichii and Neuwiedia singapureana (Apostasioideae) Reveals Different Evolutionary Dynamics of IR/SSC Boundary among Photosynthetic Orchids - Niu, Zhitao; Pan, Jiajia; Zhu, Shuying; Li, Ludan; Xue, Qingyun; Liu, Wei; Ding, Xiaoyu (Frontiers in Plant Science, 2017)
Apostasioideae, consists of only two genera, Apostasia and Neuwiedia, which are mainly distributed in Southeast Asia and northern Australia. The floral structure, taxonomy, biogeography and genome variation of Apostasioideae have been intensively studied. However, detailed analyses of plastome composition and structure and comparisons with those of other orchid subfamilies have not yet been conducted. Here, the complete plastome sequences of Apostasia wallichii and Neuwiedia singapureana were sequenced and compared with 43 previously published photosynthetic orchid plastomes to characterize the plastome structure and evolution in the orchids. Unlike many orchid plastomes (e.g., Paphiopedilum and Vanilla), the plastomes of Apostasioideae contain a full set of 11 functional NDH genes. The distribution of repeat sequences and SSR elements enhance the view that the evolution rate of non-coding regions was higher than that of coding regions. The ten loci—ndhA intron, matK-5'trnK, clpP-psbB, rps8-rpl14, trnT-trnL, 3'trnK-matK, clpP intron, psbK-trnK, trnS-psbC and ndhF-rpl32—that had the highest degrees of sequence variability (SV) were identified as mutational hotspots for the Apostasia plastome. Furthermore, plastid genes exhibit a variable evolution rate in one orchid specie and among different genera; non-coding regions evolve diversified among orchid species. Those results suggest that there is a disproportional plastome-wide variation of substitution rates among orchid species. Additionally, the sequences flanking the IR/SSC junctions of photosynthetic orchid plastomes were categorized into three types according to the presence/absence of NDH genes. Different evolutionary dynamics for each of the three IR/SSC types of photosynthetic orchid plastomes are also proposed.